Institutions and ideology in Republican Rome speech, audience and decision - Blom, Henriette van der 1977-; Gray, Christa 1982-; Steel, Catherine E. W. 1973- (Cambridge University Press, 2018)
This volume brings together a distinguished international group of researchers to explore public speech in Republican Rome in its institutional and ideological contexts. The focus throughout is on the interaction between argument, speaker, delivery and action. The chapters consider how speeches acted alongside other factors - such as the identity of the speaker, his alliances, the deployment of invective against opponents, physical location and appearance of other members of the audience, and non-rhetorical threats or incentives - to affect the beliefs and behaviour of the audience. Together they offer a range of approaches to these issues and bring attention back to the content of public speech in Republican Rome as well as its form and occurrence. The book will be of interest not only to ancient historians, but also to those working on ancient oratory and to historians and political theorists working on public speech
Keywords: Geschichte 510 v. Chr.-30 v. Chr.; Political oratory / Rome; Politische Rede; Latein; Rome / Politics and government; Römisches Reich; Aufsatzsammlung; Konferenzschrift -- 2014 -- London